The effect of public insurance coverage for childless adults on labor supply - Laura Dague; Thomas C. DeLeire; Lindsey Leininger (W.E. Upjohn Institute for Employment Research, 2014)
This study provides plausibly causal estimates of the effect of public insurance coverage on the employment of nonelderly, nondisabled adults without dependent children ("childless adults"). We use regression discontinuity and propensity score matching difference-in-differences methods to take advantage of the sudden imposition of an enrollment cap, comparing the labor supply of enrollees to eligible applicants on a waitlist. We find that enrollment into public insurance leads to sizable and statistically meaningful reductions in employment up to at least nine quarters later, with an estimated size of 2-10 percentage points, depending on the model used.
Keywords: I18; I38; J22; 330; health insurance; labor supply; employment; medicaid